Privatisation of Network Industries in Germany: A Disaggregated Approach - Günter Knieps (Albert-Ludwigs-Universität Freiburg, Institut für Verkehrswissenschaft und Regionalpolitik, 2004)
The purpose of this paper is to analyse the impact of market oriented institutional reforms in German network industries. A disaggregated approach is chosen, which differentiates between network services, infrastructure management and network infrastructure. The gradual opening of network service provision has already had a positive impact on the performance of all markets for network services. Nevertheless, harmonisation and integration of infrastructure management as well as an adequate regulation of access to the non-competitive infrastructures (monopolistic bottlenecks) is necessary in order to exploit the full benefits of liberalisation and privatisation of network service markets.
Keywords: 330; Netzzugang; Privatisierung; Infrastrukturpolitik; Deregulierung; Bottleneck; Deutschland